Kantowskie pojęcie godności a współczesne prawodawstwo - Jesiołowski, Kamil (Societas et Ius, 2018)
The aim of this article is to explain the term „human dignity”, which appears in modern constitutions and international treaties. The author included Immanuel Kant’s philosophical conceptions and indicated that it is possible to note Kantian inspirations on the ground of contemporary law. Furthermore, problems and doubts bound up with potential reception of Kant’s concepts were likewise described. The basis for the presented issues was the analysis of decisions of Polish Constitutional Tribunal and Polish law in general.